Poly(dimethylsiloxane)‐block‐PM6 Polymer Donors for High‐Performance and Mechanically Robust Polymer Solar Cells - Seo, Soodeok; Lee, Jin‐Woo; Kim, Dong Jun; Lee, Dongchan; Phan, Tan Ngoc‐Lan; Park, Jinseok; Tan, Zhengping; Cho, Shinuk; Kim, Taek‐Soo; Kim, Bumjoon J. (Advanced materials (Weinheim), 2023)
High power conversion efficiency (PCE) and stretchability are the dual requirements for the wearable application of polymer solar cells (PSCs). However, most efficient photoactive films are mechanically brittle. In this work, highly efficient (PCE = 18%) and mechanically robust (crack‐onset strain (COS) = 18%) PSCs are acheived by designing block copolymer (BCP) donors, PM6‐b‐PDMSx (x = 5k, 12k, and 19k). In these BCP donors, stretchable poly(dimethylsiloxane) (PDMS) blocks are covalently linked with the PM6 blocks to effectively increase the stretchability. The stretchability of the BCP donors increases with a longer PDMS block, and PM6‐b‐PDMS19k:L8‐BO PSC exhibits a high PCE (18%) and 9‐times higher COS value (18%) compared to that (COS = 2%) of the PM6:L8‐BO‐based PSC. However, the PM6:L8‐BO:PDMS12k ternary blend shows inferior PCE (5%) and COS (1%) due to the macrophase separation between PDMS and active components. In the intrinsically stretchable PSC, the PM6‐b‐PDMS19k:L8‐BO blend exhibits significantly greater mechanical stability PCE80% ((80% of the initial PCE) at 36% strain) than those of the PM6:L8‐BO blend (PCE80% at 12% strain) and the PM6:L8‐BO:PDMS ternary blend (PCE80% at 4% strain). This study suggests an effective design strategy of BCP PD to achieve stretchable and efficient PSCs. Polymer solar cells (PSCs) with high‐performance and ‐stretchability are developed by designing block copolymer donors comprising PM6 and elastomeric PDMS blocks (PM6‐b‐PDMS). High power conversion efficiency (PCE ≈ 18%) and stretchability (crack onset point > 18%) are demonstrated for the PM6‐b‐PDMS19k‐based PSC. The PM6‐b‐PDMS19k‐based intrinsically stretchable PSCs show superior mechanical stability (PCE retention > 80% at 32% strain) than the PM6‐based and PM6:PDMS‐blend‐based devices.